2004
DOI: 10.1385/bter:97:3:249
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical and Ultrastructural Changes in the Renal Cortex of Cadmium-Treated Rats

Abstract: The aim of this study was to determine the cadmium-induced immunohistochemical and morphological changes in the renal cortex of adult male rats exposed to high doses of cadmium for 30 d. Animals used as controls received a standard diet and water ad libitum. The animals used for this study received 15 ppm CdCl2 in their drinking water for 1 mo. The mean arterial pressure (MAP), the mean blood Cd level, and the mean tissue Cd content were significantly higher when compared to controls (p < 0.01). Immunohistoche… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
19
1

Year Published

2006
2006
2020
2020

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 22 publications
(23 citation statements)
references
References 25 publications
3
19
1
Order By: Relevance
“…Cadmium at various doses causes myelin figures; increased lysosomes; ring-shaped mitochondria; vesiculation; nuclei with dense, perinuclear chromatin [32]; and loss of microvillus [33] in the epithelia of the tubules. Immune fibronectin staining of the extracellular matrix increases [12]. Glomeruli showed increased glomerular basement membrane, irregular foot processes [12,34], widening of filtering space, and thickening of capillary vessels [35].…”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Cadmium at various doses causes myelin figures; increased lysosomes; ring-shaped mitochondria; vesiculation; nuclei with dense, perinuclear chromatin [32]; and loss of microvillus [33] in the epithelia of the tubules. Immune fibronectin staining of the extracellular matrix increases [12]. Glomeruli showed increased glomerular basement membrane, irregular foot processes [12,34], widening of filtering space, and thickening of capillary vessels [35].…”
Section: Resultsmentioning
confidence: 98%
“…The principal target of cadmium is renal proximal tubules. However, it can affect distal tubules and glomerular structures as well [12][13][14]. One of the tissue protection mechanisms against the toxic effects of cadmium is metallothionein (MT) synthesis.…”
Section: Introductionmentioning
confidence: 99%
“…It has been found that Cd produces various pathological conditions, including hepatic and renal dysfunctions, testicular damage, and respiratory and nervous system disorders (13, 14, 16,17). Cd induced chronic toxicity has been shown as histological and ultrastructural by various investigators in experiments using various species of animals (18,19). During acute exposure, Cd-induced necrosis and cellular damage are produced in the kidney, liver and testicular tissue; chronic exposure results in damage to the kidney, pancreas, and bone (20).…”
Section: Discussionmentioning
confidence: 99%
“…The second group received 15 ppm cadmium chloride monohydrate (CdCl 2, Himedia, India), and the third group received 15 ppm CdCl 2 ? 30 ppm zinc chloride (ZnCl 2, Carlo Erba, Italy) via drinking water (Asar et al 2004). Fluid intake was monitored every Toluidine blue staining was used two days.…”
Section: Methodsmentioning
confidence: 99%